PENGARUH SENAM ERGONOMIK TERHADAP PENURUNAN KADAR ASAM URAT PADA LANJUT USIA DI DESA PEMATANG KUING KECAMATAN SEI SUKA KABUPATEN BATU BARA - Rentawati Purba; Adi Arianto; Reisy Tane (Jurnal Penelitian Keperawatan Medik, 2021)
Uric acid is an inflammation of the joints caused by the accumulation of crystals in the joints due to disturbances of purine metabolism in the body. Purine is a protein that undergoes metabolism in the body which is converted into uric acid. Under normal circumstances uric acid will be excreted through feces and urine. According to WHO in Indonesia suffered from uric acid in 2018 age 34 years by 35%, age 55-64 years by 45,0%, age 65–74 years by 51,9%, age ≥75 years by 54,8%. In this case the increasing number of uric acid sufferers non-pharmacological measures such as ergonomic gymnastics which aims to help facilitate blood circulation in the body. The aims of the study to determine the effect of ergonomic exercise on reducing uric acid level in the elderly in village Pematang Kuing Sei Suka Batu Bara.This is Pre Experimental study with One Group Pre Test- Post Test design. The sampling of the technique used in the study was Purposive Sampling with a total samples of 16 elderly people. The measurement of uric acid level was done using the GCU (Glucose Uric Acid) touch easy tool. The data of the analysis technique used the Wilcoxon test to determine the effect of ergonomic exercise before and after being given therapy. The results using Wilcoxon showed that the p value was 0,000 (p<0,05). So Ha is accepted and Ho is rejected, that there is an effect of ergonomic exercise on reducing uric acid level in the elderly in village Pematang Kuing Sei Suka Batu Bara. There is an effect of ergonomic exercise on reducing uric acid level in the elderly in village Pematang Kuing Sei Suka Batu Bara.